2017
DOI: 10.1101/149120
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

To include or not to include: The impact of gene filtering on species tree estimation methods

Abstract: Abstract.-Species tree estimation from loci sampled from multiple genomes is now common, but is challenged by the heterogeneity across the genome due to multiple processes, such as gene duplication and loss, horizontal gene transfer, and incomplete lineage sorting.Although methods for estimating species trees have been developed that address gene tree heterogeneity due to incomplete lineage sorting, many of these methods operate by combining estimated gene trees and are hence vulnerable to gene tree quality. T… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 65 publications
(79 reference statements)
1
31
0
Order By: Relevance
“…The widespread adoption of methods accounting for incomplete lineage sorting is one of the major innovations made possible by phylogenomics [ 52 ], but its utility for phylogenetic inference in deep time remains a topic of discussion [ 53 , 54 ]. Simulations have demonstrated that genes with minimal phylogenetic information might produce unreliable gene trees, which in turn reduce the accuracy of species tree estimation using summary methods [ 55 , 56 ]. Our empirical analysis shows that rate heterogeneity among neognathostomate echinoids might be strong enough to bias some coalescent-based approaches, potentially by reducing the phylogenetic signal of individual genes and affecting gene tree accuracy (as recently found by other empirical studies, see [ 57 ] and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…The widespread adoption of methods accounting for incomplete lineage sorting is one of the major innovations made possible by phylogenomics [ 52 ], but its utility for phylogenetic inference in deep time remains a topic of discussion [ 53 , 54 ]. Simulations have demonstrated that genes with minimal phylogenetic information might produce unreliable gene trees, which in turn reduce the accuracy of species tree estimation using summary methods [ 55 , 56 ]. Our empirical analysis shows that rate heterogeneity among neognathostomate echinoids might be strong enough to bias some coalescent-based approaches, potentially by reducing the phylogenetic signal of individual genes and affecting gene tree accuracy (as recently found by other empirical studies, see [ 57 ] and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we also constructed a species tree with the same set of loci using SVDquartets (Chifman & Kubatko, ) in Paup* (Swofford, ). SVDquartets is expected to be more accurate than ASTRAL when there are few phylogenetically informative sites among loci, so we chose to use both of these two methods given possible biases in our loci (Molloy & Warnow, ).…”
Section: Methodsmentioning
confidence: 99%
“…Multispecies coalescence is increasingly prevalent in analyses using genomic data [34]. However, the reliability of species tree analyses can be reduced due to characteristics of individual genes such as length, missing data, and base heterogeneity that obstruct gene tree reconstruction and may increase gene tree error [35][36][37]. Gene trees are also useful for investigating discordance [38].…”
Section: Introductionmentioning
confidence: 99%